Self‐expanding transcatheter aortic valve replacement in patients with extremely horizontal aortas. (30th January 2022) - Zhou, Dao; Chen, Jun; Fan, Jiaqi; Yidilisi, Abuduwufuer; Dai, Hanyi; Xu, Yeming; Zhu, Gangjie; Guo, Yuchao; Wang, Jian'an; Liu, Xianbao
Abstract: Objectives: To evaluate the feasibility of self‐expanding transcatheter aortic valve replacement (TAVR) in patients with aortic stenosis and extremely horizontal aortas (aortic angulation ≥70°). Background: As TAVR using a self‐expanding prosthesis is an off‐label treatment for patients with extremely horizontal aortas, these patients are often excluded from randomized controlled trials involving self‐expanding TAVR. Methods: This study enrolled 27 consecutive patients with extremely horizontal aortas who underwent self‐expanding TAVR for severe aortic stenosis. Results: The patients' average age was 76.4 years, with a median Society of Thoracic Surgeons score of 4.53%. The device success and 30‐day mortality rates were 66.7% and 7.4%, respectively. The sinotubular junction (STJ) was significantly smaller in the device success group ( p = 0.001). The receiver operating characteristic curve analysis found that the area under the curve was 0.907 (95% confidence interval: 0.790–1.000, p = 0.001), validating the association between STJ diameter and device success. An optimal cutoff of 33.6 mm was determined using the Youden index, with a sensitivity and specificity of 88.9% and 77.8%, respectively. The device success rate was significantly higher (93.3% vs. 33.3%, p = 0.003) in patients with STJ diameters ≤33.6 mm ( n = 15). In the subgroup analyses, severe valve calcification ( n = 9) was associated with a higher incidence of moderate or severe paravalvular leakage (44.0% vs. 0%, p = 0.008), while a higher rate of second valve implantation (60.0% vs. 9.1%, p = 0.030) was found in patients with less than moderate valve calcification ( n = 5). Conclusion: Self‐expanding TAVR could be suitable for patients with extremely horizontal aortas after careful preoperative evaluation.